Synthesis and reactivity of 2-thionoester pyrroles: a route to 2-formyl pyrroles. Issue 54 (7th October 2019) - Kim, Min Joon; Gaube, Sophie M.; Beh, Michael H. R.; Smith, Craig D.; Thompson, Alison
Abstract : The one-step desulfurative reduction of 2-thionoester pyrroles provides 2-formyl pyrroles, including the opportunity to access the deuterated variant. Abstract : 2-Functionalised pyrroles exhibit considerable synthetic utility. Herein, the synthesis and reactivity of 2-thionoester (–C(S)OR) pyrroles is reported. 2-Thionoester pyrroles were synthesised using a Knorr-type approach from aliphatic starting materials. 2-Thionoester pyrroles were reduced to the corresponding 2-formyl pyrroles, or the deuterated formyl variant, in one step using RANEY® nickel, thereby removing the need for the much-utilised hydrolysis/decarboxylation/formylation steps that are typically required to convert Knorr-type 2-carboxylate pyrroles into 2-formyl pyrroles. 2-Thionoester pyrroles proved tolerant of typical functional group interconversions for which the parent 2-carboxylate pyrroles have become known.